French “Luiginos” and Their North Italian Imitations in the Ottoman Empire Money Cir- culation in the 1660s (Theatrum historiae, 2013)
The recognition of French small coins (5-sou), a significantly higher payment power, as legal tender in the territory of the Ottoman Empire was the reason for the imitation of those mintages in many private mints in the territory of Northern Italy in 1658–1669. Those tiny low-quality coins (called “luigino”), produced on a large scale using minting machines, were not intended for European money circulation, but only for the export to the Ottoman Empire. The author argues against the current Turkish interpretation of this phenomenon presented as a politically motivated sabotage of the then European powers. It was just a matter of business caused by long-term instability of the Ottoman Empire which Italian producers and Turkish traffickers capitalized on.
Keywords: coins; monetary circulation; 17th century; France; Ottoman Empire; Italy; luigino; economic history